Pengaruh Kualitas Produk Dan Citra Terhadap Kepuasan Konsumen Pada Usaha Kerupuk Rambak Di Kelurahan Maluhu Kecamatan Tenggarong - Soderi Wayasirli Amri (JEMI is managed and published by the Management Study Program, Faculty of Economics and Business, Kutai Kartanegara University. Institutional legality is reflected in the ISSN number: 1411-9560 published by LIPI in 2003 as a manifestation of the comm, 2019)
Absteract:In this study the object of research to be studied is the Kerupuk Rambak . Business which is a business the produks crackers, and sell crackers at addres JL: Bontang RT.04 Kel: Maluhu Kec: Tenggarong Kab: Kutai Kartanegara.With the owner Mr Mugiono, this research was made with the aim to know, whether variable product quality and image have an influence an consumer satisfaction at Kerupuk Rambak in new Maluhu village and to know among independent variable which variable is the most dominan influence on consumen satisfaction at Kerupuk Rambak.Based on the above table it can be conclu ded that the product quality and image variables simultaneously affect the consumer satisfaction. Based on the descriptions it can be concluded thet the first hypothesis peroposed states it is suspected that the product quality and image variables simultaneously affect the consumer satisfaction on Kerupuk Rambak business in new Maluhu village accepted and peroven tobe terue.From the three results of partial correlation test seen the variable value of product quality is the greatest influence than the image variable, so that the variable of product quality is the most dominant variable influencing the consumer satisfaction . From this description it can be concluded that the second hypothesis in this study it is suspected that product quality X1, dominant influence on consumer satisfaction at the blessed Kerupuk Rambak in new Maluhu village is accepted and peroven to be terue.